2008
DOI: 10.1515/jpm.2008.082
|View full text |Cite
|
Sign up to set email alerts
|

Premature labor: a state of platelet activation?

Abstract: Normal pregnancy is a state in which there is a physiologic increase of sCD40L. PTL was associated with an increased median maternal plasma sCD40L concentration that could not be accounted for by IAI. Thus, our findings suggest that platelet activation occurs during an episode of preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 142 publications
(185 reference statements)
0
22
1
1
Order By: Relevance
“…Substantial evidence indicates that intra-amniotic inflammation is a risk factor for adverse pregnancy and neonatal outcome, regardless of the presence or absence of a positive AF culture [2, 79, 16,25,33,34]. However, the data presented herein demonstrates that a culture-proven infection has clinical implications beyond the presence of intra-amniotic inflammation with a negative AF culture in preterm PROM.…”
Section: Commentmentioning
confidence: 71%
“…Substantial evidence indicates that intra-amniotic inflammation is a risk factor for adverse pregnancy and neonatal outcome, regardless of the presence or absence of a positive AF culture [2, 79, 16,25,33,34]. However, the data presented herein demonstrates that a culture-proven infection has clinical implications beyond the presence of intra-amniotic inflammation with a negative AF culture in preterm PROM.…”
Section: Commentmentioning
confidence: 71%
“…Each of these pathways is central in the deployment of an inflammatory response: cytokine-cytokine receptor interaction, Jak-STAT signaling, the complement and coagulation pathway, NOD-like receptor signaling, systemic lupus erythematosus (specifically the complement C1q complex), and chemokine signaling. Interestingly, components of these pathways have been previously linked to both normal parturition [57, 75, 76, 159, 180, 201, 213, 221, 226–228, 235, 271, 274, 308] and the “Great Obstetrical Syndromes” [32, 33, 64, 7982, 84, 85, 89, 238, 267, 291, 295, 307, 320], including preterm labor [28, 58, 74, 77, 83, 8688, 119, 120, 164, 165, 211, 223, 246, 252, 254, 290, 292, 293, 316319]. Indeed, our group has reported an association between activation of the NALP3 inflammasome and the common pathway of parturition [119].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-amniotic inflammation (regardless of the presence or absence of proven intra-amniotic infection) is associated with adverse pregnancy outcome [9, 23, 38, 48]. Recent studies revealed that various chemokines [11, 14, 16, 18, 21, 29, 30], as well as traditional proinflammatory cytokines such as the interleukin family [3, 13, 19, 45] and MMPs [4, 10, 27, 32], play a role in the pathogenesis of intra-amniotic infection/inflammation and preterm parturition.…”
Section: Commentmentioning
confidence: 99%